The immunoregulatory effect of the TREM2-agonist Sulfavant A in human allogeneic mixed lymphocyte reaction - Barra, Giusi; Gallo, Carmela; Carbone, Dalila; Ziaco, Marcello; Dell’Isola, Mario; Affuso, Mario; Manzo, Emiliano; Nuzzo, Genoveffa; Fioretto, Laura; D’Ippolito, Giuliana; De Palma, Raffaele; Fontana, Angelo (Frontiers in Immunology, 2023)
Introduction Sulfavant A (SULF A) is a synthetic derivative of naturally occurring sulfolipids. The molecule triggers TREM2-related maturation of dendritic cells (DCs) and has shown promising adjuvant activity in a cancer vaccine model. Methods the immunomodulatory activity of SULF A is tested in an allogeneic mixed lymphocyte reaction (MLR) assay based on monocyte-derived dendritic cells and naïve T lymphocytes from human donors. Flow cytometry multiparametric analyses and ELISA assays were performed to characterize the immune populations, T cell proliferation, and to quantify key cytokines. Results Supplementation of 10 µg/mL SULF A to the co-cultures induced DCs to expose the costimulatory molecules ICOSL and OX40L and to reduce release of the pro-inflammatory cytokine IL-12. After 7 days of SULF A treatment, T lymphocytes proliferated more and showed increased IL-4 synthesis along with downregulation of Th1 signals such as IFNγ, T-bet and CXCR3. Consistent with these findings, naïve T cells polarized toward a regulatory phenotype with up-regulation of FOXP3 expression and IL-10 synthesis. Flow cytometry analysis also supported the priming of a CD127-/CD4+/CD25+ subpopulation positive for ICOS, the inhibitory molecule CTLA-4, and the activation marker CD69. Discussion These results prove that SULF A can modulate DC-T cell synapse and stimulate lymphocyte proliferation and activation. In the hyperresponsive and uncontrolled context of the allogeneic MLR, the effect is associated to differentiation of regulatory T cell subsets and dampening of inflammatory signals.